OPTIMASI PENAMBAHAN NUTRIEN TERHADAP KADAR PROTEIN PADA FERMENTASI PADAT KULIT UMBI UBI KAYU MENGGUNAKAN RESPONSE SURFACE METHODS (RSM) - Erna Juliarti; Iis Alfaizah (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2013)
Cassava is tropic and subtropic tree from Euphorbiaceae family and Manihot esculenta as binomial name. The aims of fermentation of cassava peel to decrease of agroindustry waste and used for animal feed. The waste from agroindustry contain carbohydrate and little protein. To reduce the waste needed fermentation process to enriched protein content using saacharomyces cereviceae. This experimental using cassava peel was drying at the first. The experimental design used was 23 full factorial central composite design with 18 run was consist of 8 run on second level (-1/+1), 6 run star points (-1.68/+1,68), and 4 run replication on centre points (0). The data was obtain analyzed using Respons Surface Methods (RSM) to know optimum condition such as: vitamin B1 total, water content, and C/N ratio on solid state fermentation of cassava peel. The result shown that maximum yield of protein reached at 36.40 % with vitamin B1 at 0.0100 %, water content at 65 %, and C/N ratio at 15. The value of cyanide acid also decrease from 0.024 % to 0.009 % after 6 days fermentation process.